Effects of Positive Expiratory Pressure on Gas Exchange, Atelectasis, Hemodynamics, and Dyspnea in Spontaneously Breathing Critically Ill Subjects. - Masuello, Denise; Servetti, Adriano; Caiffa, Salvatore; Cara, Robertina; Pieri, Chiara; Arriagada, Ricardo; Al-Husinat, Lou'i; Ball, Lorenzo; Robba, Chiara; Brunetti, Iole; Patroniti, Nicolò; Silva, Pedro Leme; et al. (Respiratory Care, 2025)
Background: The EzPAP Positive Airway Pressure System (EzPAP) is a noninvasive positive expiratory pressure (PEP) device designed to promote lung expansion. The aim of this study was to evaluate the effects of PEP on gas exchange. Secondary objectives included assessing the early effects of PEP on radiological atelectasis score (RAS), hemodynamics, and dyspnea. These outcomes were compared between spontaneously breathing subjects with and without tracheostomy. Methods: This observational single-center study was conducted at a university hospital. Inclusion criteria were spontaneously breathing adult subjects with RAS ≥ 2 and a worsened PaO2/FIO2. Exclusion criteria included life-threatening conditions, intracranial hypertension, hemodynamic instability, and pneumothorax. Gas-exchange, hemodynamic parameters, and dyspnea measured with the Respiratory Distress Observation Scale (RDOS) were assessed at 3 time points: T0 (before PEP), T1 (immediately after PEP), and T2 (2 h after PEP). RAS was assessed at T0 and 1-week post treatment (T3). Results: Of 213 patients assessed for eligibility, 186 were excluded for various reasons, leaving 27 subjects (19 without and 8 with tracheostomy) enrolled in the study. The median [interquartile range] age was 65 [58–74] y, with 66.7% being male. In the overall sample and in subjects without tracheostomy, PaO2/FIO2 did not differ significantly between T1 and T0 (P =.52 and P =.54, respectively) or between T2 and T0 (P =.47 and P =.85, respectively). In subjects with tracheostomy, PaO2/FIO2was higher at T1 compared to T0 (P =.039) but not between T2 and T0 (P =.58). Arterial PaO2 and hemodynamic parameters remained unchanged in the overall cohort. The RAS improved within 1 week of treatment in the overall cohort (T3 vs T0, P < .001) and in subjects without tracheostomy (T3 vs T0, P =.001). However, PEP therapy did not improve RDOS. Conclusions: In critically ill, spontaneously breathing subjects, PEP therapy significantly improved RAS without affecting hemodynamic stability or respiratory symptoms.